Pemberdayaan Siswa Kader KS di Bidang Kesehatan Mata dan Kewirausahaan (Membentuk Generasi Sadar Mata Sehat dan Pencipta Peluang) di SMP 22 Kota Semarang: (Forming a Generation that is Aware of Healthy Eyes and Creator of Opportunities) at SMP 22 Semarang City - Didik Wahyudi; Mochammad Kholil; Mahbub Junaedi; Edvi Gracia Ardani (Lembaga Pengembangan Kinerja Dosen, 2026)
Empowering student health unit (UKS) cadres in the areas of eye health and entrepreneurship is crucial for preventing visual impairment and fostering a smart and productive generation. This activity aims to improve the quality of life and future of students through health education, eye health services used in learning, vision care, and entrepreneurship. The benefits of this educational activity include increased understanding of health, particularly regarding visual impairment and its management, preventing visual impairment, and enhancing entrepreneurial knowledge and skills. This community service activity utilizes a participatory educational method, prioritizing a needs-based approach for the target partners, namely junior high school students and, in particular, the UKS cadres. The activity was conducted in stages and divided into several main phases to ensure effective and sustainable transfer of knowledge and skills. The activity was conducted in several main sessions involving all 440 students in grades 7 and 8, including 27 UKS staff. The results of this community service program include increased knowledge of junior high school students about healthy vision, awareness of maintaining near and far vision within normal limits through healthy behaviors in using the sense of sight. Students' understanding of entrepreneurship from outside sources is also enhanced, as students have already received entrepreneurship lessons. However, information provided by outside sources will further strengthen and inspire them to create opportunities that align with their interests and talents. The skills of the Health Unit (UKS) cadres in conducting visual acuity checks independently and with peers are expected to be conducted periodically and routinely every three months, and incidentally if needed or if someone needs it due to complaints of decreased vision. The eye health and entrepreneurship education model can serve as a reference for other schools. It needs to be implemented continuously and in stages, in line with technological developments and the latest health policies.